Phenotypes of α1-antitrypsin in liver diseases - MIYAKE, Kazuhiko; SUZUKI, Hiroshi; ODA, Toshitsugu; OKA, Hiroshi (Kanzo, 1980)
α1-antitrypsin phenotypes were detcrmined by polyacrylamide gel slab isoelectric focusing in the samples of 648 normal subjects and 761 patients with liver diseases. Three common PiM subtypes (M1M1, M1M2, M2M2) were classified and the allele frequencies estimated fbr PiM1 and PiM2 were 0.82 and 0.18, respectively. α1-antitrypsin in serum was on the lowest level in M2M2 (M1M1>M1M2>M2M2). In 761 patients with liver diseases we found 416 M1M1 (54.7%), 256 M1M2 (33.6%), 79 M2M2 (10.4%) and 10 rare variants (1.3%)-2 Etokyo M1, 1 Etokyo M2, 1 IM1, 1 M1N, 1 M1P, 3M2P, 1M1S. Of 648 normal subjects, there were found 447 M1M1 (69.0%), 164 M1M2 (25.3%), 32 M2M2 (4.9%) and 5 rare variants (0.8%)-2 Etokyo M1, 1 IM1, 2M1N. 1) Frequencies of rare variants were quite low as compared with those in the European populations, and none of Z gene Was detected. 2) Four heterozygotes fbr PiP were detected in a group of liver diseases. 3) A significant difference in M2M2 frequency was found between patients with liver diseases and controls (p<0.001). P and M2M2 might be predisposing factors to the developing of liver diseases.